Knowledge, attitudes and practices of medical students towards electronic learning in a tertiary care centre in central India: a cross-sectional study - Pandey, Shreshtha; Bhelkar, Sandeep; Narlawar, Uday W. (International Journal Of Community Medicine And Public Health, 2022)
Background: Medical education is constantly growing at a rapid speed and to keep the upcoming doctors in par with the competitive world e-learning has become a necessary tool. In pandemic situations like COVID-19, instructors must deliver lectures safely as well as ensure the integrity and continuity of the medical education process. Online classes became a key component in the continuity of education. It is therefore important to determine the knowledge, attitudes, and practices of medical students regarding electronic medical education. Methods: A cross sectional study was conducted among 325 undergraduate medical students and interns in a tertiary care centre in central India using probability proportional to size sampling. The study involved a KAP questionnaire towards e-learning that was distributed as Google form by means of social media. Results: Study participants belonged to the age group of 18-30 years. 54% were male and 46% were female. 95.4% study participants used smart phones for medical education. 89.1% used online applications and platforms for medical education purposes. 84.6% used the internet regularly in your studies. 60.3% disagreed that e-learning can cover practical aspect of medical education. Conclusions: Study results show that medical students had optimistic attitude, good knowledge and practice towards electronic learning. E-learning is a useful tool to ensure continuity of medical education as well as helpful in minimizing the effects of pandemics like COVID-19 on medical education and on the progression of training.